Perbandingan Religiusitas Tokoh Mualaf dalam Novel Ayat-ayat Cinta Karya Habiburrahman El-Shirazy dan Novel Ternyata Aku Sudah Islam Karya Damien Demarta - Wulandari, Vivi; Nurizzati, Nurizzati; Zulfadhli, Zulfadhli (Universitas Negeri Padang, 2012)
The article of this study were to describe the religiositas muallaf the figure in Ayat-ayat Cinta novel opus Habiburrahman El-Shirazy with Ternyata Aku Sudah Islam novel opus Damien Dematra, comparison the religiositas muallaf the figure in Ayat-ayat Cinta novel with Ternyata Aku Sudah Islam novel. The data of this study were religiositas muallaf the figure in Ayat-ayat Cinta novel with Ternyata Aku Sudah Islam novel. The primary source of data were Ayat-ayat Cinta novel and Ternyata Aku Sudah Islam novel. Data were collected by describtion method. The findings of the study showed that religious muallaf the figure in Ayat-ayat Cinta novel and Ternyata Aku Sudah Islam novel. Then, so comparison religiositas muallaf figure in Ayat-ayat Cinta and Ternyata Aku Sudah Islam.